Secure and energy-efficient smart building architecture with emerging technology IoT - Kumar, Arun; Sharma, Sharad; Goyal, Nitin; Singh, Aman; Cheng, Xiaochun; Singh, Parminder (Computer communications, 2021)
With the advent of the Internet-of-Things (IoT), it is considered to be one of the latest innovations that offer interesting opportunities for different vertical industries. One of the most relevant IoT technology areas is smart construction. IoT operates in several sectors on a daily basis; implementation includes smart building, smart grids, smart cities, smart houses, physical defense, e-health, asset, and transportation management, but it is not restricted to this. Support from smart IoT buildings is an IoT-level, connected, and cost-effective system. Commercial space has major requirements in terms of comfort, accessibility, security, and energy management. Such requirements can be served organically by IoT-based systems. As the supply of energy has been exhausted and energy demand has risen, there has been a growing focus on energy usage and the maintenance of buildings. With the use of evolving IoT technology, we present a secure and energy-efficient smart building architecture. Every device is known by its unique address, and one of the key web transfer protocols is the Constrained Application Protocol (CoAP). It is an application layer protocol that does not use protected channels for data transfer. Automatic key management, confidentiality, authentication, and data integrity are all features of the Datagram Transport Layer Protection (DTLS). To achieve energy efficiency, we propose a smart construction architecture that, through IoT, manages the performance of all technological systems. The results of the simulation show that the energy consumption is lowered by about 30.86% with the use of the CoAP in the smart building, which is less than the Message Queuing Telemetry Transport case (MQTT). This paper also aims to observe how to integrate the DTLS protocol with the Secure Hash Algorithm (SHA-256) using optimizations from the Certificate Authority (CA) to improve security.